Conceptions of Political Representation and its Application in Thai Politics - Piyakulchaidech, Wanas; Meesuk, Eakkawee (King Prajadhipok’s Institute Journal, 2024)
Political representation is one of the most essential concepts in the contemporary political era, especially in democratic regimes. However, the concept faces the same problem as other political concepts (such as justice, rights, equality, etc.), in that one idea has several conceptions. Whenever the idea was transliterated from the Western to a political context in Thailand, the concept was twisted and stretched by incorporating the original meanings with new connotations. This research presents the meanings and conceptions of political representation from the Western context and its application in Thai politics. It also suggests a plausible concept. The analysis assumes that the idea of political representation affects and shapes Thai politics, but the Thai political context reduces the idea’s impact and its applications. The constitutional drafting committee is more concerned with the problems of election fraud than with how the representatives effectively represent the needs and the interests of the voters. The researchers use documentary research to portray the various conceptions of political representation and its adaptation to Thai political contexts. This research also interviews some members of the drafting committee of the current constitution as critical informants to view the adaptation of the very ideas and their limitations. The idea of political representation was categorized into three main conceptions: delegation, trustee and advocated. By comparing these three conceptions, the researchers find that the advocacy conception is the most suitable for capturing the complexity of political phenomena, and it overcomes the limitation of the other two contesting concepts. The advocacy conception presents the process that connects the represented (voters, citizens in the constituency), and representatives with the election and other political processes (recall, press) to create the dialectic relationship between the represented and the representatives. From the perspective of applying the concept, the interview results confirm the assumption that the drafting committee is primarily concerned with the problem of fraud in elections.